Inhibition of integrated stress response protects against lipid-induced senescence in hypothalamic neural stem cells in adamantinomatous craniopharyngioma. Issue 4 (1st December 2022) - Wang, Chaohu; Zhang, Huarong; Fan, Jun; Li, Qing; Guo, Rongrong; Pan, Jun; Liu, Yawei; Peng, Junxiang; Zhu, Qianchao; Feng, Yiwen; Wu, Chengdong; Luo, Peng; et al.
Abstract: Background: Adamantinomatous craniopharyngioma (ACP) is a benign tumor with malignant clinical manifestations. ACP adjacent to the hypothalamus often presents with more severe symptoms and higher incidence of hypothalamic dysfunction. However, the mechanism underlying hypothalamic dysfunction remains unclear. Methods: Immunostaining was performed to determine the nerve damage to the floor of the third ventricle (3VF) adjacent to ACP and to examine the recruitment and senescence of hypothalamic neural stem cells (htNSCs). The accumulation of lipid droplets (LDs) in htNSCs was evaluated via BODIPY staining, oil red O staining, and transmission electron microscopy. In vitro and in vivo assays were used to evaluate the effect of cystic fluid or oxidized low-density lipoprotein and that of oxytocin (OXT) on htNSC senescence and the hypothalamic function. The protein expression levels were analyzed using western blotting. Results: htNSCs with massive LD accumulation were recruited to the damaged 3VF adjacent to ACP. The LDs in htNSCs induced senescence and reduced neuronal differentiation; however, htNSC senescence was effectively prevented by inhibiting either CD36 or integrated stress response (ISR) signaling. Furthermore, OXT pretreatment reduced lipotoxicity via the inhibition of ISR signaling and the repair of the blood–brain barrier. Conclusions: Reduced LD aggregation or ISR signaling inhibition prevented senescence in htNSCs and identified molecular pathways and potential therapeutic targets that may improve hypothalamic dysfunction in ACP patients. Graphical Abstract: